The trend of international tourist arrivals to Malaysia / Sharina Abd Rahim - Abd Rahim, Sharina (Faculty of Business and Management, 2010)
This research examines the trend of international tourist arrivals to Malaysia. Furthermore, this research also aims to examine the factors affecting the tourist arrivals and the factors leading to the tourist arrivals. The economic factors, motivation, marketing and promotion, safety, security and health and other factors have been studied. Based on the secondary data obtained, the finding suggests that marketing and promotion successfully increase the tourist arrivals to Malaysia. Moreover, it is also found that Malaysia is considered a safe haven for tourist, as it is not prone to natural disasters or terrorist attacks. The study also focuses on examining the relationship between tourist arrivals and tourist receipts. It was founded that there are a significant relationship between tourist arrivals and tourist receipts. This means that, the increase of tourist arrivals will increase the tourist receipts. Therefore, the government should allocate an appropriate budget for the tourism industry in order to carry out the promotional activity to further increase tourist arrivals. Other than that, a stronger relationship between government, local authorities, private agencies and hotel operators should be fostered to ensure that the tourists’ needs, especially in potential markets can be fulfilled. Furthermore, it is also recommended that subsequent research should have an in-depth study of the characteristics of visitors from various origins and destination, as it was seen that, the trend of international tourist arrivals vary from one other. Therefore, the industry players should co-operate to design the promotions and marketing specifically for the different markets.